2011
DOI: 10.1007/s10103-011-0981-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the erbium:yttrium-aluminum-garnet laser or diamond bur cavity preparation on the marginal microleakage of class V cavities restored with different adhesives and composite systems

Abstract: The aim of this in vitro study was to compare the microleakage of Er:YAG laser and diamond bur on different bonding systems in class V restorations. Class V cavities were prepared with Er:YAG laser or diamond bur on 80 intact human molars. Teeth were randomly distributed into ten groups and cavities were restored with CeramX duo (DENTSPLY) or Filtek Silorane (3M/ESPE) using different bonding materials (One Coat 7.0 (Coltène), XP Bond (DENTSPLY), Clearfil Protect Bond (Kuraray), AdperSE (3M/ESPE), and Silorane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
1
13
1
7
Order By: Relevance
“…When comparing microleakage between enamel and dentin margins for all groups and each one of the samples individually, dentinal margins demonstrate vastly larger amounts of dye penetration. In agreement with this observation is a summation of the published literature 1,3,8,10,12,23,[27][28][29][30]32,37,38,44,45 . This agreement can be attributed to the more difficult and technically sensitive procedure involving adhesion to dentin 8 , as well as to the more complex and reduced inorganic content of the dentin compared to enamel 1 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…When comparing microleakage between enamel and dentin margins for all groups and each one of the samples individually, dentinal margins demonstrate vastly larger amounts of dye penetration. In agreement with this observation is a summation of the published literature 1,3,8,10,12,23,[27][28][29][30]32,37,38,44,45 . This agreement can be attributed to the more difficult and technically sensitive procedure involving adhesion to dentin 8 , as well as to the more complex and reduced inorganic content of the dentin compared to enamel 1 .…”
Section: Discussionsupporting
confidence: 82%
“…Although the mechanical, physical and esthetic properties of contemporary composites have improved in comparison to their predecessors, polymerization shrinkage and its related stress remain a major concern which requires improvement 3,4 . Achieving good marginal sealing remains a considerable challenge in composite restorations 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The latter system also presented lower microleakage at the dentin margins than Clearfil S 3 Bond. 16 Yaman et al 17 found lower microleakage for XP Bond (a twostep etch-and-rinse system) compared to One Coat 7.0. Owens and Johnson 18 found lower performance at the enamel margins and higher sealing at the dentin margins using Xeno IV and Clearfil S 3 Bond, respectively, as compared to iBond and G-Bond.…”
Section: Discussionmentioning
confidence: 99%
“…When teeth are subjected to mechanical stress, because of difference in modulus of elasticity of tooth and restoration, the integrity of restoration-tooth margin deteriorates over a period of time [3,10,24,25]. Use of lasers for cavity preparation has not shown any improvement in microleakage sealing when compared to the conventional diamond bur preparation, highlighting the importance and need of suitable restorative material [26]. The use of silorane based composites has also been suggested for restoration of class V cavities in a recent study [27].…”
Section: Discussionmentioning
confidence: 99%